(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2002)
Behavior-analytic research has contributed for the identification of variables affecting the repertoires of autistic individuals. This work is aimed at the identification of methodological variations in behavior-analytic production with this population. The analysis of studies on autism identified two different – although complementary – veins of research. One vein seems to emphasize the identification of variables acting on the establishment of stimulus control. The other vein aims at the establishment and maintenance of verbal behavior. The methodological features described are: the nature of the stimuli and the criteria for choosing them, the kinds of required responses, and of consequences presented. Some considerations are made about the benefits of attending to methodological demands of behavior-analytic research. Also discussed is the role of behavior analysts concerning the relative lack of studies on the issue and the need for the development of prevention and educational programs for parents and relatives of autistic individuals.